Governing Open Ocean and Fish Carbon: Perspectives and Opportunities - Oostdijk, Maartje; Elsler, Laura G.; Ramírez-Monsalve, Paulina; Orach, Kirill; Wisz, Mary S. (Frontiers in Marine Science, 2022)
Marine life plays a vital role in the ocean’s biological pump by sequestering and mediating fluxes of carbon to the deep sea and sea floor. The roles that fish and other marine vertebrates play in the biological pump are increasingly attracting scientific and policy attention. In this paper, we investigated the interest in and possibilities for the international governance of open ocean and fish carbon ecosystem services. We used semi-structured interviews with representatives from environmental non-governmental organisations (ENGOs), policy makers, and policy experts, along with an exploratory review of grey and peer-reviewed literature to: 1) trace the pathway of important milestones, key actors, and their strategies to influence governance of ocean carbon, and, 2) investigate which frameworks might be used to govern open ocean and fish carbon. Strategies of key actors to direct attention to open ocean and fish carbon included collaborating with scientists, organising side events at climate and biodiversity negotiations and seminars to engage policy makers, as well as educational campaigns directed to the public and policy makers about the co-benefits of open ocean and fish carbon. While we found a strong focus of ENGO activities related to the UN Framework Convention on Climate Change, we also found strong opposition against active governance of open ocean and fish carbon by key Intergovernmental actors in this forum. Opposition stems from a lack of scientific information on how long open ocean and fish carbon is stored, difficulties in attributing carbon flows with individual countries mitigation actions, and fewer perceived co-benefits (e.g. coastal protection in the case of coastal blue carbon) for coastal communities. More viable routes for the future governance of open ocean and fish carbon may lie in international fisheries management and in current negotiations of a treaty for biodiversity conservation in the high seas.